Association of blood progesterone levels on trigger day and low oocyte retrieval in cases with polycystic ovary syndrome undergoing in-vitro fertilization: A prospective cohort study - Nahid Bahrami; Ashraf Moini; Ladan Kashani; Mahshad Khodarahmian (International Journal of Reproductive BioMedicine)
Background: The number of follicles aspirated during intracytoplasmic sperm injection (ICSI)/in vitro fertilization (IVF) treatment does not always match the number of oocytes recovered.